2018
DOI: 10.1073/pnas.1719579115
|View full text |Cite
|
Sign up to set email alerts
|

Modeling environmentally mediated rotavirus transmission: The role of temperature and hydrologic factors

Abstract: Rotavirus is considered a directly transmitted disease due to its high infectivity. Environmental pathways have, therefore, largely been ignored. Rotavirus, however, persists in water sources, and both its surface water concentrations and infection incidence vary with temperature. Here, we examine the potential for waterborne rotavirus transmission. We use a mechanistic model that incorporates both direct and waterborne transmission pathways, coupled with a hydrological model, and we simulate rotavirus transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 48 publications
(59 reference statements)
6
42
0
Order By: Relevance
“…While rotavirus transmission is typically considered to occur via direct person-to-person contact, this result highlights the importance of environmental transmission via water in Dhaka. This is consistent with recent studies showing that rotavirus transmission is sensitive to interannual variation in flooding [8], and that waterborne transmission alone is sufficient to spread the virus between hydrologically connected locations [7]. The use of tubewells has also been shown to provide a protective effect against other diarrheal diseases in Bangladesh, such as cholera [11,12] and shigellosis [12], especially in areas that are not protected from flooding [13].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While rotavirus transmission is typically considered to occur via direct person-to-person contact, this result highlights the importance of environmental transmission via water in Dhaka. This is consistent with recent studies showing that rotavirus transmission is sensitive to interannual variation in flooding [8], and that waterborne transmission alone is sufficient to spread the virus between hydrologically connected locations [7]. The use of tubewells has also been shown to provide a protective effect against other diarrheal diseases in Bangladesh, such as cholera [11,12] and shigellosis [12], especially in areas that are not protected from flooding [13].…”
Section: Discussionsupporting
confidence: 89%
“…Bangladesh is an example of a country with high incidence all year round, particularly in Dhaka the capital city, where high temperatures, low humidity, and flooding events have been associated with an increased risk for rotavirus [6]. Current dogma suggests that person-to-person contact is the dominant mode of transmission of the virus, although it has been shown to persist in water [7] and to respond to climatic changes [8]. Dhaka has more than 18 million inhabitants and a population growth of about 4% annually, making it one of the densest and fastest growing megacities in the world.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Understanding mechanisms by which pathogens transmit between hosts is key for defining disease risk and for planning effective control strategies. In addition to direct host‐to‐host or vector‐borne transmission, pathogens can spread through environmental sources, such as through contact with fomites (Allerson, Cardpna, & Torremorell, ), ingestion of contaminated drinking water (Breban, ; Kraay et al, ), contact with contaminated soil (Turner et al, ), contact with contaminated carcasses (Chenais, Ståhl, Guberti, & Depner, ), or carcass scavenging (Brown & Bevins, ; Wille et al, ). Environmental sources of infection can promote pathogen persistence by increasing their likelihood of contact with susceptible hosts because many pathogens can remain viable in the environment longer than they can keep a host infectious.…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of infectious agents in environmental reservoirs can enable high pathogen reproductive numbers when epidemic growth rates are low by extending the infectious period beyond the life expectancy of the host (Almberg, Cross, Johnson, Heisey, & Richards, ). In some systems, environmental transmission mechanisms can explain recurrent epidemics (Towers et al, ), even at intervals that are longer than demographic cycling (Breban, ), as well as amplifying rates of interpopulation transmission by increasing infectious contact opportunity between groups (Kraay et al, ). Theoretical metapopulation modeling has shown that accounting for mechanisms of environmental transmission in addition to routes of direct transmission can lead to qualitatively different disease dynamics and predict different animal movement thresholds for metapopulation decline (Park, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation